Bezpieczeństwo bankowości internetowej - Solarz, Małgorzata (Internet banking safety, 2005)
Internet banking appeared in Poland six years ago. Since then the number of Internet bank accounts has been increasing dynamically. At the end of June 2004 there were already 2,7 million of them. The number of Internet banking users would be even bigger if not the reported lack of the feeling of safety while communicating with the bank by means of www. site. Clients are afraid that the information on their bank accounts and the data referring to performed operations may be broken into or modified by criminals. In order to prevent this banks use different types of safety measures related to the scope of their using the Internet as banking services distribution channel. Among them there are: so called firewalls, data transmission coding by means of SSL protocol, simple and complex authorization. The letter is carried out by means of single use pass words printed on a TAN card or generated by a token. Among the methods of complex authorization there are also these which use an electronic signature.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1091, s. 119-129